Entrepreneurship and its analysis in Colombia: A contextualized literature review. (2015)
This paper presents a literature review contextualized through the different stagesof Colombian industrial history up to the first decade of the XXI century, whenan attempt is made to organize the growing interest in the topic of entrepreneurship.We find a tight connection between public policy agenda setting and the definitionof the research agenda of the topic. We also find a dualistic approach in theresearch of the topic, with universities and think-tanks leading the investigation on accumulative / innovative entrepreneurship, and a consultancy-bias group dedicated to the study of subsistence entrepreneurship.